Types of narcissistic self-regulation in the context of personal fulfillment - Klymenko, Maria (Journal of Education Culture and Society, 2019)
Aim. The aim of the research is to generalize different types of "healthy" narcissistic Self-regulation and to disclose the specific of self-fulfillment and personal life satisfaction.Method. The empirical study involved 360 Ukrainian students (N=360), aged from 17 to 24. The following research methods were used F. W. Deneke and B. Hilgenstock’s Narcissism Inventory (1989), A. Längle and C. Orgler’s Scale of Existence (2003), E. Diener’s Satisfaction with Life Scale (1985), D. Polhus and C. Williams’s "Dark Triad of Personality" questionnaire (2002). The obtained data were processed by multivariate statistics (Statistica 8.0 and Exel), using cluster and comparative analysis (Student's t-test, Scheffe Test).Results. The analysis shows that the most effectively functioning narcissistic self-regulation type is characterized by high narcissism that goes together with the high self-power. The personal fulfillment indicators (such as: self-distance, self-transcendence, freedom, responsibility, existentialism, and personality) are also growing in such conditions. Adequate narcissistic self-regulation goes together with the more meaningful relations with reality and enrichment of the person’s internal emotional life. With the growth of narcissism raises rather positive life acceptance and affirmative attitudes towards “Being” and oneself in it.Conclusions. Narcissistic self-regulation is a mechanism that cares about the stability and integrity of the self-system, makes it possible to accept and appreciate one’s own personality. Only through the prism of prizing oneself (high, but functional narcissism) the value of other people and the world could be seen. This opens the possibility to find and fulfill the meaning of existence.